SOCIAL STUDIES-HISTORICAL LEARNING SYSTEM FOR GEN-Z IN THE NEW NORMAL ERA - Jossapat Hendra Prijanto (PROGRES PENDIDIKAN, 2022)
The COVID-19 pandemic has affected the education system, namely new normal learning; therefore, a contextual learning model is needed in accordance with the needs students, namely Gen-Z. The research method uses the literature reviews obtained through books, articles, and journals. The results of the research are that social studies-history learning in the new normal era is a new challenge for teachers, where they have to make use of social media in dealing with the generation that is close to the Internet, which results in shaping their character as the generation that is creative, innovative, and broad-minded. Therefore, learning provided is student-centered learning, and involves learning conducted online or offline. This research concludes that in building the social studies-history learning system for Gen-Z in this new normal situation, it requires a change in the curriculum that is flexible, innovative, and creative, and according to the students’ model called Gen-Z.